(untitled) - Lide, David R. (Boca Raton, Florida, 1998)
The 79th edition of the Hamdbook of Chemistry and Physics features updates and expansions of a number of tables, as weel as the introduction of several new topics. Among the new tables are: * Diamagnetic susceptibility of selected organic compounds * Magnetic susceptibility of the elements and inorganic compounds * Spectroscopic constants of diatomic molecules * Dielectric strength of insulating materials * Carbohydrate names and symbols * global temperature trend, 1866-1996
Keywords: Chemistry,Physics